Abuse of Authority in the Banking Sector as a Form of Corporate Crime - Indra Gunawan Purba (Britain International for Academic Research (BIAR) Publisher, 2026)
Abuse of authority in the banking sector constitutes one form of economic crime that has significant implications for customer protection, the stability of the financial system, and the level of public trust in the banking industry. The practice of abuse of authority by internal banking organs, including directors, commissioners, officers, and employees, is often manifested in the form of fictitious credit disbursement, manipulation of financial data, misuse of customer funds, and violations of the prudential banking principle. The central issue lies in the fact that law enforcement against banking crimes in Indonesia still tends to focus on individual liability, while the involvement of corporations as legal entities has not been optimally enforced. This study aims to analyze the forms and characteristics of abuse of authority in the banking sector that may be qualified as corporate crimes, to examine the legal regulation of corporate criminal liability for abuse of authority in the banking sector in Indonesia, and to formulate a model of corporate criminal liability capable of realizing legal certainty, justice, and utility. This research employs a normative legal research method using the statute approach, conceptual approach, and case approach. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed qualitatively using a juridical-prescriptive method. The findings reveal that abuse of authority in the banking sector is not always an individual act but may be qualified as a corporate crime when there is a connection between individual actions and organizational structure, business interests, corporate benefit, institutional omission, or failure of the bank’s internal supervisory system. The legal framework governing corporate criminal liability has essentially been established through banking regulations, criminal law, and procedural mechanisms for handling corporate crimes. However, its implementation still faces normative and practical obstacles. Therefore, a corporate criminal liability model based on the integration of individual and corporate liability, the strengthening of good corporate governance, compliance systems, and a corporate negligence approach is necessary to improve the effectiveness of combating abuse of authority in the banking sector.